Self-confidence and its relationship to the effectiveness of the skillful performance of the smashing hit by players of the specialized volleyball school. (Al-Muthanna Journal of Sport Education Sciences, 2026)
The importance of this research lies in measuring the level of self-confidence and identifying the relationship between the effectiveness of the volleyball spike technique among players of the specialized school. Research Problem: Researchers, through their monitoring of Premier League and age-group sports teams, observe a clear decline in the level of these teams, resulting from weak individual and collective performance, a fact well-known in the community. The athlete interested in this sport understands that this weakness is not primarily the player's fault, especially if they possess good physical attributes suitable for the activity they are practicing. In this case, the coach bears the greater part and the primary responsibility, along with providing the necessary resources and requirements for the training process. The importance of this research lies in finding solutions. The appropriate approach involves developing specific exercises that take into account these mental and psychological variables, understanding their impact and relationship to the effectiveness of skill performance in volleyball. Research objectives: To identify the relationship between self-confidence level and the effectiveness of the spiking skill performance of volleyball players. Research hypothesis: There is a relationship between self-confidence level and the effectiveness of the spiking skill performance of volleyball players. Self-confidence and the effectiveness of the spiking technique in volleyball players. The research area: Human element: Volleyball players aged 15-17 years at the specialized school. The research methodology, based on the nature of the research problem, employed a descriptive approach using correlational relationships. The population The research sample: The researcher defined the research population in a purposive manner, which consisted of 48 young volleyball players aged (15-17 years) in Baghdad, from the clubs (Specialized School, Industry, Police, Housing). The research sample was chosen in a random manner, which consisted of players from the Specialized School. In volleyball, the sample consisted of 12 players, representing 25% of the population. Conclusions: Based on the statistical analysis of the results obtained from the research sample, and after presenting, analyzing, and discussing the findings, the researcher reached the following conclusions: A significant correlation was found between self-confidence as a variable and performance effectiveness. The Skillful Smash Recommendations: Based on the conclusions reached by the researcher, they recommend the following: Focusing on adopting exercises similar to match situations or offensive and defensive formations that occur during competition and matches, due to their significant role in developing the player's skillful and tactical abilities. Coaches analyze their teams’ matches, evaluate them, and present them to the players to increase their awareness and discover their mistakes, especially for junior and youth teams and their lack of experience